Hydrotreating Model Comparison of Raw Castor Oil and its Methyl Esters for Biofuel Production. Issue 1 (20th November 2018) - Mederos-Nieto, Fabián S.; Elizalde-Martínez, Ignacio; Hernández-Altamirano, Raúl; Trejo-Zárraga, Fernando; Mena-Cervantes, Violeta Y.; Ramírez-Jiménez, Edgar; Vallarta-Cardona, Daniela E.
Abstract: Some of the main problems during vegetable oil hydrotreating are the high heat of reaction released, the huge quantity of expensive hydrogen required, and the high corrosion rates in the equipment. Some insights into the advantages and disadvantages of processing raw vegetable oils or their respective fatty acid methyl esters are given. The ASPEN Plus process simulator was used for the simulation of a hydrotreating process, with two different feedstocks coming from the same plant: raw castor oil and castor oil methyl esters. That process was modeled with two stoichiometric reactors in series. The technical viability of using methyl esters as hydrotreating feedstock for the production of biofuels such as green gasoline and diesel is demonstrated. Abstract : Some advantages of hydrotreating fatty acid methyl esters from castor oil seeds instead of their triglycerides are elucidated. Benefits and disadvantages of processing raw vegetable oils or their respective fatty acid methyl esters are investigated. The technical feasibility of employing methyl esters as hydrotreating feedstock for biofuel production such as green gasoline and diesel is highlighted.